2012
DOI: 10.1016/j.physleta.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Nanogroove array on thin metallic film as planar lens with tunable focusing

Abstract: Numerical results for the distributions of light transmitted through metallic planar lenses composed of symmetric nanogroove arrays on the surfaces of a gold film are presented and explained.Both the near-and far-field distributions of the intensity of light transmitted are calculated by using a Green's function formalism. Results for an optimal transverse focus based on a quadratic variation of groove width are obtained. Meanwhile, a significant dependence of the focal length on the wavelength of light incide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…If we treat the SIBC in Eqs. (13), (14), (15) and (16) as a perturbation for small η L and η R , we can express A s (β), A a (β), B s (β) and B a (β) by the discrete Fourier expansion coefficients a j sn , b j sn , a j an and b j an to the leading order of the perturbation. Alternatively, if only the diagonal contributions for the term proportional to η L or η R are kept 3,11,16 in Eqs.…”
Section: This Leads Tomentioning
confidence: 99%
See 3 more Smart Citations
“…If we treat the SIBC in Eqs. (13), (14), (15) and (16) as a perturbation for small η L and η R , we can express A s (β), A a (β), B s (β) and B a (β) by the discrete Fourier expansion coefficients a j sn , b j sn , a j an and b j an to the leading order of the perturbation. Alternatively, if only the diagonal contributions for the term proportional to η L or η R are kept 3,11,16 in Eqs.…”
Section: This Leads Tomentioning
confidence: 99%
“…Alternatively, if only the diagonal contributions for the term proportional to η L or η R are kept 3,11,16 in Eqs. (13), (14), (15) and (16) [i.e., including only the terms with β = ±β in the integrals], A s (β), A a (β), B s (β) and B a (β) can also be expressed by the discrete Fourier expansion coefficients a j sn , b j sn , a j an and b j an . However, such a simplification 3,11,16 needs to be justified physically.…”
Section: This Leads Tomentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study , 7 we have shown the longitudinally color-dependent light focusing by a finite linear array of grooves with various widths in a parabolic pattern, where various focal lengths of a slit-array aperture were obtained for an incident plane wave with different colors. Here, rather than using a Green's function formalism , 8,9 we present a scattering-wave theory which utilizes slit-eigenmode expansion to treat an arbitrary array of slits having arbitrary spacings, width and dielectrics.…”
Section: Introductionmentioning
confidence: 99%